FACEBOOK SEBAGAI RUANG TUBUH DIGITAL: PEMBACAAN WACANA KRITIS NORMAN FAIRCLOUGH IDENTITAS MELALUI KONSEP TUBUH TANPA ORGAN - Faidil, M; Hasbi, Nur (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2025)
This study analyzes the representation of women's bodies in Facebook content using Norman Fairclough's Critical Discourse Analysis (CDA) approach and the concept of the body without organs from Gilles Deleuze and Félix Guattari. The research method used is descriptive qualitative with Fairclough's three-dimensional discourse analysis technique, namely text analysis, discourse practice, and social practice. Data in the form of six visual and textual posts from Facebook were selected purposively based on the intensity of the representation of women's bodies. The results of the analysis show that women's bodies are represented as visual objects produced through power relations between digital affect, social media algorithms, and patriarchal cultural narratives. In the perspective of the body without organs, the body is no longer understood as a whole and fixed entity, but rather as an affective field that is fluid, fragmented, and continues to be shaped by the intensity and network of desire. This study emphasizes the importance of reading women's bodies on social media as a site of discourse production and a field of resistance, as well as opening up a space for reflection on digital technology that also shapes contemporary body subjectivity